Pengaruh Trietanolamin Dan Asam Stearat Terhadap Mutu Fisik Dan Stabilitas Mekanik Krim Sari Buah Tomat - Aditya Rahma Mudhana; Anasthasia Pujiastuti (Indonesian Journal of Pharmacy and Natural Product, 2021)
Tomatoes contain lycopene which is an antioxidant. Antioxidant preparations can be made in the form of a cream with components of an oil phase, a water phase and an emulsifier. Emulsifiers that can be used are triethanolamine (TEA) and stearic acid. This study aims to determine the effect of triethanolamine and stearic acid as emulsifiers on the physical quality and mechanical stability of tomatoes extract cream. The use of triethanolamine and stearic acid with a ratio of 2%:5%; 3%:10%; 4%:15%. The test are the physical characteristics of tomatoes extract cream included organoleptic, homogeneity, cream type, pH, viscosity, spreadability, adhesion, protection and mechanical stability using the centrifugation method. The results of the phytochemical screening of tomatoes extract were positive for triterpenoids. The test results of the three cream formulas are odorless, semi-solid form, light orange to white color, homogeneous, cream type M/A, pH 5.25 - 6.26; viscosity 5,376 cP - 14,370 cP, spreadability 4 - 5,067 cm, adhesion 4 - 11.6 seconds, protection power 2 - 5.2 seconds. The three cream formulas did not undergo phase separation. The higher concentration of TEA and stearic acid had an effect on viscosity, pH value, adhesion, dispersibility and protection, but had no effect on organoleptic, homogeneity, cream type, and stability. tomatoes extract cream with a concentration of TEA:stearic acid 2%:5% gave the best physical quality.